Jejunal diverticulitis as a cause of acute abdomen - Cantão,Cássio Alfred Brattig (2016)
ABSTRACT Jejunoileal diverticulosis is an uncommon and underdiagnosed condition. Most patients are asymptomatic and require no specific treatment. A few patients, however, present life-threatening complications that may require surgical intervention. The purpose of this report is to illustrate a case of jejunoileal diverticulosis manifested as an acute abdomen.